Rate of Loaded Sediments in Honda Bay, Puerto Princesa City, Palawan, Philippines - Becira, Joel (Science Diliman: A Journal of Pure and Applied Sciences; Vol 18 No 1 (2006))
A study in Honda Bay, Puerto Princesa City, Palawan, Philippines was conducted to determine and compare the rate of loaded sediments of and among six sites in Honda Bay and during two seasons, and to discuss sedimentation rate in relation to selected environmental parameters commencing on April 2003 to November 2003. Results showed that the Babuyan River significantly contributed to the amounts of sediments being loaded to Honda Bay, Puerto Princesa City of which the amount of sediments loaded between the two sampling season and among the six sampling events had no significant difference. Sediment's color and texture affirmed the land-based activities in Babuyan and Mauyon watersheds, which eventually carried into the Bay during storm weather condition. The amount of trapped sediments in all stations is probably affected by the river's discharge capacity and the river's water velocity, although the duration sediment traps were mounted could also affect the measurement of sedimentation rate.